Comparison of factors that affect the quality of life of Korean land police officers and maritime police officers - Han, Seung-Woo; Yoon, Hyun-Seok (Frontiers in Psychiatry, 2025)
BackgroundThe quality of life (QoL) of land police officers (LPOs) and maritime police officers (MPOs), involves not only their work life but also their personal life, including their interactions with family and friends.MethodsThis study was conducted with LPOs and MPOs based in Region J of South Korea. Data were collected from September 1 to September 30, 2024. Instruments used included measures of job satisfaction, leisure satisfaction, self-esteem, and overall quality of life. Data were analyzed using stepwise multiple regression.ResultsFor LPOs, the factors that significantly affect the QoL were subjective health status (‘moderate’, β = -0.213, p = .001; ‘poor’, β = -0.130, p = .021), job satisfaction (β = 0.414, p = .001) and leisure satisfaction (β = 0.393, p = .001). These variables explained 64.2% of the variance in QoL. For MPOs, the factors that significantly affect the QoL were low economic level (β = -0.440, p = .007), job satisfaction (β = 0.269, p = .001), leisure satisfaction (β = 0.488, p = .001), and self-esteem (β = 0.164, p = .006). These variables explained 53.2% of the variance in QoL.ConclusionThe findings of this study indicate a clear need to implement counseling interventions to improve the quality of life of LPOs and MPOs. Additionally, to improve their overall quality of life, programs to enhance physical and mental health must be developed.